Microdispositivos a Base de Papel para análise de Drogas de Abuso - Reis, Jadson Zeni dos (2024)
The growing consumption of illicit drugs in Brazil has worried society, the resources used by drug traffickers are evolving exponentially. Therefore, it is necessary that the technology used to combat drugs also evolves. The main drugs in the country are made up of a large number of substances and analyzing them requires work. One of the modern techniques capable of discerning substances in a mixture is microfluidics, which is attributed to small samples of fluid in small channels. The technique has aspects, the most prominent being the one that uses paper, as it is cheaper. In this work, paper microfluidics was revised for application in two tests, the first being modified by Scott in order to calculate the hydrochloride content in seized samples of cocaine and crack. The other test applied uses a Cobalt II Thiocyanate solution, test with Fast Blue B, to evaluate the content of some of the cannabinoids present in marijuana samples. However, the pure visual analysis of the colorimetric response is influenced by several factors, hence the use of a smartphone camera to make the technique more precise. However, like any chemical analysis, the Scott test and the Fast Blue B test have variables and varying them separately is very expensive work that clashes with reality. Therefore, to minimize this problem, the work was assisted by experimental planning in the factorial model in the search for optimal conditions for spot size and reagent content, which influence the results. Other chemometric tools such as principal component analysis and partial least squares were used to evaluate whether the samples grouped together and a possible prediction of responses. It is also interesting to highlight that the high selectivity of the µPAD, Micropaper-based analytical device, suggests the possibility of using the technique to identify these narcotics even when dissolved in dark liquids.